ANALISIS PENGEMBANGAN POTENSI WISATA TKL ECOPARK SEBAGAI WISATA UNGGULAN KOTA MAGELANG - Andini Ayuningtyas; Sekar Ayu Damayanti; Muhammad Arif Kurniawan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Magelang City is one of the cities in Central Java that has the potential for tourist attractions. There are various tourism objects presented by the City of Magelang to tourists who visit, one of which is TKL-Ecopark. This study aims to identify, support policy development and provide alternative strategies for managing the development of tourism potential in TKL-Ecopark. The research method this time uses qualitative and quantitative methods. The data collection technique in this study using questionnaire instruments and population and samples in this study is the management of TKL Ecopark (Taman Kyai Langgeng Ecopark) Magelang City which is the mainstay tourism of Magelang City. The method used is to combine the SWOT (Strengths, Weaknesses, Opportunities, Threats) matrix and QSPM (Quantitative Strategic Planning Matrix).